Analysis of Dental and Oral Health Outpatient Visits at Baturiti II Public Health Centre - I Wayan Agus Wirya Pratama; Ni Putu Idaryati; Ilma Yudistian; I Dewa Gede Ananta Wibhu; I Gusti Agung Ngurah Anindya Kresnayana; Ida Ayu Amara Tarisya Paramisuari; Komang Hesty Pradnyani; Ni Kadek Meidy Xanaya Putri (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Public Health Centers play a vital role in providing comprehensive and affordable healthcare services to the community. Baturiti II Public Health Centre, with an extensive service area covering a population of 18,893, is responsible for managing medical records and analyzing patient visit data. This study aims to collect empirical data and conduct an in-depth analysis of the outpatient visit patterns in the dental and oral health service unit. Materials and Methods: This study employs a descriptive quantitative analysis method using a total sampling technique to collect outpatient visit data from the dental and oral health service unit of Baturiti II Public Health Centre throughout 2023. Data were collected through medical record document review, and the results are presented in tables and diagrams. Results and Discussion: The analysis of patient visits to the dental and oral health service unit at Baturiti II Public Health Centre in 2023 recorded a total of 1,141 visits, consisting of 559 new patients and 582 follow-up patients, with the majority using the National Health Insurance (JKN) as the financing mechanism. The peak of new patient visits occurred in December, while follow-up patients peaked in June. The most prevalent diseases were pulp and periapical tissue diseases (41%), followed by persistence (24%), gum and periodontal tissue diseases (19%), dental caries (11%), and tooth impaction (5%). There was a tendency for males to experience pulp diseases and caries more frequently, while females more often experienced persistence, periodontal diseases, and tooth impaction, with hormonal, anatomical, and behavioural factors contributing to gender disparities. Conclusion: Patient visits were dominated by new patients using the JKN financing mechanism. Pulp and periapical tissue diseases were the most prevalent cases, particularly among male patients.